Indonesia’s New Penal Code: Harmonizing with Global Justice or Defying International Norms? - Arifin, Ridwan; Alkadri, Riska; Smith, Robert Brian; Smith, Nucharee Nuchkoom; Wahyudin, Wahyudin (Lex Scientia Law Review, 2024)
This study critically examines Indonesia's new penal code through the lens of international legal norms, exploring whether it genuinely embodies the principles of global justice. Despite the code's ambitious reforms aimed at modernizing Indonesia's legal framework, our analysis reveals significant gaps between its provisions and internationally accepted standards, particularly in areas such as human rights, due process, and equality before the law. The urgency of this research lies in Indonesia's important role in Southeast Asia, where legal frameworks can influence regional governance and human rights practices. Novelty arises from our comparative approach, juxtaposing Indonesia’s penal code against a backdrop of global legal norms while considering local cultural and societal contexts. This study uncovers how the interplay between domestic priorities and international expectations can lead to compromises that undermine the integrity of justice. Our findings contribute to the ongoing discourse on legal reform in emerging democracies, highlighting the challenges of aligning national legislation with international standards. By providing concrete recommendations for policy makers, legal practitioners, and civil society, this research emphasizes the need for a holistic approach to legal reform that respects both local values and global commitments. Ultimately, we argue that Indonesia's new penal code is not just a legal document but a reflection of its aspirations for justice, demanding scrutiny and ongoing dialogue to ensure it meets the standards of global justice in practice.